Temperance And Racism : John Bull, Johnny Reb, and the Good Templars - Fahey, David M. (Book collections on Project MUSE., 2015)
One hundred twenty years ago, the Independent Order of Good Templars was the world's largest, most militant, and most evangelical organization hostile to alcoholic drink. Standing in the forefront of the international temperance movement, it was recognized worldwide as a potent social and moral force. Temperance and Racism restores the Templars, now an almost forgotten footnote in American and British social history, to a position of prominence within the temperance movement. The group's ideology of universal membership made it unique among fraternal organizations in the late nineteenth centur.